VD_FINDINFO HC / 2012 / 5 vom 21. November 2011 - VD Tribunal cantonal (2011)
DIVORCE, MESURE PROVISIONNELLE, OBLIGATION D'ENTRETIEN, ENFANT, CONJOINT | 176 al. 1 ch. 1 CC, 276 al. 1 CPC (CH), 276 al. 2 CPC (CH), 308 al. 1 let. b CPC (CH), 312 al. 1 CPC (CH)